2013
DOI: 10.1186/1472-6947-13-82
|View full text |Cite
|
Sign up to set email alerts
|

How do medical doctors use a web-based oncology protocol system? A comparison of Australian doctors at different levels of medical training using logfile analysis and an online survey

Abstract: BackgroundElectronic decision support is commonplace in medical practice. However, its adoption at the point-of-care is dependent on a range of organisational, patient and clinician-related factors. In particular, level of clinical experience is an important driver of electronic decision support uptake. Our objective was to examine the way in which Australian doctors at different stages of medical training use a web-based oncology system (http://www.eviq.org.au).MethodsWe used logfiles to examine the character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Using the infrastructure of electronic health records for clinical DSS could support personalized medicine practices by providing the tailored information at the right time. Various researchers have discussed the advantages of incorporating DSS in electronic health records in combination with smart algorithms, such that continuous updating and rapid adaptation of DSS are ensured [11,[24][25][26][27]. This precision oncology should be a multidisciplinary effort incorporating information from various experts and stakeholders [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the infrastructure of electronic health records for clinical DSS could support personalized medicine practices by providing the tailored information at the right time. Various researchers have discussed the advantages of incorporating DSS in electronic health records in combination with smart algorithms, such that continuous updating and rapid adaptation of DSS are ensured [11,[24][25][26][27]. This precision oncology should be a multidisciplinary effort incorporating information from various experts and stakeholders [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…These tools are developed to decide whether certain treatments bring enough gain in overall or progressionfree survival to be worthwhile for patients. Research has shown that oncologists tend to overestimate life expectancy of patients [7,8], and that they could benefit from using statistical tools providing survival estimates [7,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, it is possible the lack of adherence could be due to deficiencies of the guidelines themselves. However, independent evaluations of the eviQ guidelines suggest that clinicians are aware of and accessing the guidelines . Additionally, the guidelines are recommended as a useful resource in the literature…”
Section: Discussionmentioning
confidence: 99%